INTERRELATIONSHIPS OF SMOOTH AND NONSMOOTH VARIANTS IN THE DISSOCIATION OF PASTEURELLA HAEMOLYTICA - Wessman, G. E. (1964)
Wessman, G. E. (National Animal Disease Laboratory, U.S. Department of Agriculture, Agricultural Research Service, Ames, Iowa). Interrelationships of smooth and nonsmooth variants in the dissociation of Pasteurella haemolytica. J. Bacteriol. 88:356–360. 1964.—Smooth Pasteurella haemolytica, after rapid growth in statically incubated broth cultures, decreased in numbers rapidly, and were replaced by nonsmooth variants. Upon continued incubation, smooth cells again predominated. The two phenotypes were alike in general biochemical characteristics, but differed in virulence for mice. The presence of nonsmooth cells in mixed cultures severely limited the growth of smooth cells. The inhibition of smooth cells correlated with the establishment of definite population densities, and the critical factor appeared to be limitation of oxygen in the cultural medium. Selective inhibition did not occur in aerated cultures, but was more pronounced in cultures grown under reduced air pressure. Selective death of smooth cells on slant cultures held at 5 C and preferential growth of nonsmooth cells, plus death of smooth cells at room temperature, accounted for population changes in stored cultures.